Prothrombotic gene mutations and Crohn's disease; is there any association? - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2005)
Background/Aims: Patients with inflammatory bowel disease have an increased tendency for thromboembolism. In this study we aimed to determine the frequency of FV gene and Prothrombin G20210A gene mutations in a group of patients with Crohn's Disease (CD) and estimate its correlation with disease activity and clinical subtype. Methodology: Forty-four CD patients and 43 healthy controls were included in the study. Twenty-three of the patients had inflammatory CD, while 11 had fibrostenotic and 10 had fistulizing CD. Only one patient had a history of deep vein thrombosis. Polymorphisin Light Cycler FV Leiden mutation detection kit and Light Cycler prothrombin (G20210A) mutation detection kit were used for the detection of mutations in DNA samples. Results: Forty of the CD patients had normal factor V genotype, three (6.8%) patients showed a heterozygous, and one (2.3%) patient homozygous pattern. Two (4.7%) of the 43 controls showed heterozygous factor V mutation and 41 had normal FV genotype. Two (4.6%) CD patients had heterozygous prothrombin G20210A mutation, and there was only one (2.3%) homozygous mutation in the control group. There was no significant difference between controls and CD patients neither for factor V mutation (p > 0.05) nor for prothrombin G20210A mutations (p > 0.05). No correlation was found between disease activity and both gene mutations (p>0.05), as well as between disease subtype and gene mutations (P > 0.05). Conclusions: The prevalence of prothrombin G20210A gene and factor V Leiden gene mutations were found to be statistically insignificant among CD patients and control group.
Keywords: inflammatory bowel disease; thromboembolism; FV gene and prothrombin; G20210A gene mutations; Crohn's disease; INFLAMMATORY-BOWEL-DISEASE; ACTIVATED PROTEIN-C; V-LEIDEN MUTATION; VENOUS THROMBOSIS; COAGULATION; RESISTANCE; THROMBOPHILIA; G20210A; REGION; RISK